Midwife’s Knowledge and Attitude in Kangaroo Mother Care To Premature Neonatal in the Public Health Centre in Batang - Samsuri, Muhammad Taadi; Kholifah, Kholifah; Sukini, Tuti; Astuti, Tulus Puji (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
One of indicators in the successful health affair in a country is the number of infant mortality rate. Causes of mortality among others are respiratory disorders 37%, prematurity 34%, sepsis12%, hypothermia7%, post mature 3% and congenital defect 1% and blood defect or icterus 6%. Infant mortality due to hypothermia can be prevented by practical method as an alternative to incubator namely Kangaroo Care Method. The implementation of Kangaroo Care Method must be monitored and evaluated by health care provider especially the midwife. This research was conducted in 2015.The purpose of this research was to find out the correlation between midwivesÃ¢â‚¬â„¢ knowledge and their attitude in implementing Kangaroo Method to premature infant.This research was observasional with design cross sectional approach. The number of population was 65 midwives and as a sample 49 midwives. The data were collected by means of questionnaire. Data analyses used bivariate Spearman rho test. The result of the research showed that 32 midwives (65.3%) had good knowledge and most of 27 midwives (55.1%) had positive attitude. It was obtained from Spearman rho test ÃÂ value 0.001 and correlative coefficient (r) 0.696. The conclusion, there was any close correlation between knowledge and attitude of midwives in kangaroo care method.